2004
DOI: 10.1002/dc.20112
|View full text |Cite
|
Sign up to set email alerts
|

Cytological diagnosis of cystic brain tumors: A retrospective study of 88 cases

Abstract: The stereotaxic aspiration of cystic brain tumors is performed to provide cyst decompression and/or to facilitate surgical resection. The purpose of our study was to determine the diagnostic value of brain cyst fluid cytology, especially in clinically suspected recurrent tumors with no histological follow-up (HF), when a diagnosis is most needed. We reviewed the cytological diagnoses of 88 aspirates from 70 patients with cystic brain tumors between 1995 and 2001, of which 31 had a prior known malignancy includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…R. mackenziei was almost always reported in individuals residing in the Middle East 2,4 whereas Exophiala dermatitidis is frequently seen in Asia. 14 On the other hand, Silverman et al gave support for the value of fine needle aspiration (FNA) biopsy in diagnosing lesions of the central nervous system. 12 Cerebral phaeohyphomycosis carries a high mortality rate of 73%.…”
Section: Discussionmentioning
confidence: 99%
“…R. mackenziei was almost always reported in individuals residing in the Middle East 2,4 whereas Exophiala dermatitidis is frequently seen in Asia. 14 On the other hand, Silverman et al gave support for the value of fine needle aspiration (FNA) biopsy in diagnosing lesions of the central nervous system. 12 Cerebral phaeohyphomycosis carries a high mortality rate of 73%.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação às lesões císticas, houve maior discrepância entre os diagnósticos histopatológico e citopatológico em razão de o exame do conteúdo do cisto ser freqüentemente inconclusivo, enquanto a biópsia da parede cística revela quase sempre a natureza da lesão. Esses dados estão de acordo com o estudo realizado por Hernandez et al (39) , no qual o exame citopatológico do material aspirado de lesões cerebrais císticas de natureza neoplásica, incluindo tumores cerebrais primários e adenocarcinomas metastáticos, evidenciou elevado índice de resultados falso-negativos e baixa sensibilidade, principalmente para tumores cerebrais primários de origem glial, que mostram escassa tendência a esfoliar. O material aspirado, mesmo após centrifugação e confecção de esfregaço a partir do sedimento, consistiu principalmente em sangue lisado, células inflamatórias e células degeneradas, produzindo resultados inconclusivos.…”
Section: Estudos Sobre Be De Lesões Acometendo Estruturas Intracraniaunclassified
“…Abnormal vascular proliferation is an important feature in the histological and cytological diagnosis of tumours, including brain tumours. However, cytological analysis of the vasculature of primary gliomas or metastatic brain tumours is rarely reported . This study showed that microvascular proliferations were frequent in metastatic tumours, whereas none were identified in normal/reactive brain tissues and the majority of grade II DA/ODGs.…”
Section: Discussionmentioning
confidence: 71%